2011
DOI: 10.1037/a0022709
|View full text |Cite
|
Sign up to set email alerts
|

Why do overqualified incumbents deviate? Examining multiple mediators.

Abstract: In the modern marketplace, especially when unemployment is high, more and more Americans find themselves overqualified (i.e., possessing more competencies than the job requires). Using and extending person-environment fit theory and the stressor-emotion model of counterproductive work behaviors (CWBs), we examine whether overqualified employees are more likely to display CWBs than employees who feel their positions match their qualification levels. Further, we examine why overqualified employees may behave in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
192
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(255 citation statements)
references
References 133 publications
(243 reference statements)
13
192
3
7
Order By: Relevance
“…Having a career in the occupation was possible only with the necessary skills and knowledge that are often acquired through education and training. This result was in line with earlier research (Luksyte et al, 2011) that showed that a match between job and qualification was positively related to a relational and balanced contract. Both studies conveyed the message that the appropriate qualification was related to a long-term employment relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Having a career in the occupation was possible only with the necessary skills and knowledge that are often acquired through education and training. This result was in line with earlier research (Luksyte et al, 2011) that showed that a match between job and qualification was positively related to a relational and balanced contract. Both studies conveyed the message that the appropriate qualification was related to a long-term employment relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Luksyte et al (2011) found that the graduates have participated in the work of the investigation, if employees feel overqualified, dissatisfaction and pressure, boredom and other negative emotions and appear because of their own capacity is not fully utilized, will lead to counterproductive work behavior [2]. The results of Bolino & Feldman (2000) show that the higher the perception is, the worse the subjective performance is.…”
Section: A the Relationship Between Perceived Over Qualificationmentioning
confidence: 99%
“…Although the relationship between job burnout and CWB has been examined less frequently, there is evidence for the link between emotional exhaustion and CWB. More frequently CWB occurred among emotionally exhausted employees (Banks et al, 2012) or among employees who scored high on Downloaded by [Central Michigan University] at 17:01 08 October 2015 cynicism (Luksyte, Spitzmueller, & Maynard, 2011), which may be considered as one of the dimensions of burnout. Further, Krischer et al (2010) showed that the employees who engaged in production deviance (e.g., deliberately performing work slowly or incorrectly) and withdrawal behaviors (e.g., leaving work earlier than allowed) experienced less emotional exhaustion than employees who refrained from those behaviors.…”
Section: Job Demands-cwb Relationship and The Mediating Role Of Job Bmentioning
confidence: 99%